Increase in hospital admission rates for heart failure in The Netherlands, 1980-1993. Issue 5 (November 1996) - Reitsma, J. B.; Mosterd, A.; de Craen, A. J.; Koster, R. W.; van Capelle, F. J.; Grobbee, D. E.; Tijssen, J. G.
Abstract : OBJECTIVE: To study the trend in hospital admission rates for heart failure in the Netherlands from 1980 to 1993. DESIGN: All hospital admissions in the Netherlands with a principal discharge diagnosis of heart failure were analysed. In addition, individual records of heart failure patients from a subset of 7 hospitals were analysed to estimate the frequency and timing of readmissions. RESULTS: The total number of discharges for men increased from 7377 in 1980 to 13 022 in 1993, and for women from 7064 to 12 944. From 1980 through 1993 age adjusted discharge rates rose 48% for men and 40% for women. Age adjusted in-hospital mortality for heart failure decreased from 19% in 1980 to 15% in 1993. For all age groups in-hospital mortality for men was higher than for women. The mean length of hospital admissions in 1993 was 14.0 days for men and 16.4 days for women. A review of individual patient records from a 6.3% sample of all hospital admissions in the Netherlands indicated that within a 2 year period 18% of the heart failure patients were admitted more than once and 5% more than twice. CONCLUSIONS: For both men and women a pronounced increase in age adjusted discharge rates for heart failure was observed in the Netherlands from 1980 to 1993. Readmissions were a prominent feature among heart failure patients. Higher survival rates after acute myocardial infarction and the longer survival of patients with heart disease, including heart failure may have contributed to the observed increase. The importance of advances in diagnostic tools and of possible changes in admission policy remain uncertain.